Mediating integration: Latino immigrant organizations in greater Boston - Escobar, Cristina; Moran, Amy; Lima, Álvaro; Melnik, Mark (REMHU, Revista Interdisciplinar da Mobilidade Humana, 2010)
In recent years scholars have debated the role of immigrant organizations in the processes of integration, political incorporation, and transnational activities (for example, Huntington 2004; Portes and Rumbaut 2006; Bloemraad 2006; Portes, Escobar and Walton 2006). The current research adds to this discussion through a case study of selected immigrant organizations from Greater Boston’s largest Latino immigrant communities. Through qualitative interviews with leaders of immigrant organizations we found that connections and alliances matter for integration. Immigrant-led organizations are unique because of their leadership and proximity to the community. Even groups focused on cultural, religious, and transnational activities serve as informal mediators in the integration process. They provide practical information, support, and connections to mainstream society. Our findings inform how local governments can leverage the position of immigrant organizations to build social and human capital in marginalized communities. Working with these informal networks allows the government to increase the efficiency and quality of its outreach to immigrants.Keywords: Integration; Immigration Organizations; TransnationalismNos últimos anos, estudiosos têm debatido o papel das organizações de imigrantes no processo de integração, incorporação política e transnacional (por exemplo, Huntington 2004; Portes e Rumbaut 2006; Bloemraad 2006; Portes, Escobar e Walton 2006). Este projeto acrescenta a esta discussão através de um estudo de caso focado num grupo de organizações das maiores comunidades imigrantes latinas da Grande Boston. Através de entrevistas qualitativas com líderes destas organizações, descobrimos que conexões e alianças são fundamentais no processo integração. Organizações de imigrantes têm caracteres únicos devido à sua liderança e proximidade com a comunidade. Mesmo  os grupos focados em atividades culturais, religiosas e atividades transnacionais servem como mediadores informais no processo de integração. Eles fornecem informações práticas, apoio e ligações a sociedade mainstream. Os resultados da pesquisa em questão informam como governos locais podem alavancar o trabalho das organizações de imigrantes para construir capital social e humano nas comunidades marginalizadas. Trabalhar com essas redes informais permite ao governo aumentar a eficiência e a qualidade da sua atuação junto à populações imigrantes.Palavras-chave: Integração; Organizações de imigrantes; Transnacionalismo